nvestigating the Influence of Lifestyle Attitudes on the Pedagogical Responses of Pupil Teachers towards Sustainable Development Goals (SDGs) - Kumar, Neelesh (JOURNAL OF INDIAN EDUCATION, 2024)
The Sustainable Development Goals (SDGs) have grown significantly in the educational sector. It is essential to examine the factors influencing student teachers’ pedagogical responses with the SDGs. Lifestyle perspectives are one such element that may affect how pupil teachers approach teaching about sustainable development. The study employed a particular observational survey methodology to examine how lifestyle attitudes affect how pupil teachers approach teaching about the SDGs. A sample of 220 student teachers from a teacher training school was recruited using stratified random sampling. A questionnaire was used to gather information about student teachers’ lifestyle attitudes and pedagogical responses to the SDGs. The data analysis employed a structured questionnaire. The findings revealed a statistically significant positive association between lifestyle attitudes and student teachers’ pedagogical responses to the SDGs. Particularly, it was discovered that student teachers with healthy lifestyle perspectives have more effective pedagogical responses to the SDGs. Furthermore, it was shown that student teachers who had undergone SDG training reacted to the goals more positively from a pedagogical perspective. The study demonstrates that SDG training helps encourage supportive pedagogical responses to sDGs. The study discusses the significance of developing quality pedagogical responses to SDGs among student teachers through training on SDGs and lifestyle perspectives. The findings have significance for institutions that educate teachers and decision-makers who want to advance sustainability education and meet the sDGs.